Risk of malnutrition in the elderly of Bragança - Parente, Alexandra Mariza de Egas Geraldes (2016)
Malnutrition affects a significant number of people, the elderly being the main group affected. Retrospective studies highlight that the elderly are at higher risk and have higher susceptibility of nutritional defidencies than young adults. Objective: To assess the risk of malnutrition in the elderly of Bragança. Methods Analytical and cross-sectional study. Based on a sampling error under 5 % and a confidence levei of 95 %, a sample of 385 elderly people stratified by gender and age was studied. A questionnaire was used including nutritional risk assessment using the Mini Nutritional Assessment (MNA). Results 56.4 % (217) are women and 43.6 % (168) are men with an average Of 76.39 ± 7. 18 years of age. The majority (62. 9 %; 242) is married/civil partnership and 28.6 % (110) are widowers. 37.8 % (134) relate some degree of loneliness. We also noticed that 96 elderly (24.9 %) show risk of malnutrition. Those who are married/in a civil partnership have higher probability of normal nutritional condition when compared with single or divorced (OR = 2.925); those with schooling have higher probability of normal nutritional condition (OR= 2.287) compared to those without schooling. The ones who mention less loneliness present 1.5 to 4.7 higher probabilities of normal nutritional condition compared with the ones who state any levei of loneliness. The ones who are functionally independent have higher probability of a normal nutritional state than those who have any degree of dependency. Conclusions Results highlight the need for spedfíc protocols in health institutions to identify old people at nutritional risk allowing a timely intervention.